Attention, Impulsiveness, and Gender in Academic Achievement Among Typically Developing Children - Alavi, Masoumeh; Seng, J.; Mustaffa, M.S.; Ninggal, M.T.; Amin, Mansour; Latif, A.A. (SAGE Publications Inc., 2019)
Although several studies have examined the relationships among attention, impulse control, gender, and academic achievement, most have focused on clinical samples and have considered only one or two academic subjects. This study investigated these relationships among typically developing children using general achievement measures (academic scores and grades). Our participants were 270 typically developing primary school students (142 boys and 128 girls) of different nationalities living in Malaysia, recruited with purposive sampling with a mean age of 9.75 years. We found that both attention and impulse control significantly predicted academic achievement. Girls had a higher level of attention and impulse control than boys, but gender was not a significant moderator between either attention or impulse control and academic achievement. We discuss the implications of these findings and the need for further research. © The Author(s) 2018.